Persepolis [book club bag] - Satrapi, Marjane, 1969- (Random House, 2004)
[This is the author's] memoir of growing up in Iran during the Islamic Revolution.... [She] tells the story of her life in Tehran from ages six to fourteen, years that saw the overthrow of the Shah's regime, the triumph of the Islamic Revolution, and the devastating effects of war with Iraq--Jacket flap.